The complex relationship between estrogen and migraines: a scoping review - Reddy, Nihaal; Desai, Miraj N.; Schoenbrunner, Anna; Schneeberger, Steven; Janis, Jeffrey E. (Systematic reviews, 2021)
Background Migraines are a chronic disease for millions worldwide and have been hypothesized to be hormonally mediated due to their higher prevalence in females and menstrual associations. Estrogen has been commonly implicated in migraine pathogenesis, yet its exact role in the pathophysiology of migraines has yet to be fully understood. Method We conducted a scoping review of the literature regarding estrogen’s role in migraine pathogenesis and included 19 studies out of an initial 202 in the final review. Two independent reviewers screened and extracted data from included studies based on predetermined inclusions and exclusion criteria. Results The estrogen withdrawal hypothesis, discussed by 12 of the reviewed studies, is the most discussed theory about estrogen’s role in migraine physiology and describes the association of migraine onset with natural declines in estrogen levels, particularly when estrogen levels fall below 45–50 pg/mL after an extended period of priming. Additional findings suggest that women with a history of migraine have an increased sensitivity to physiologic fluctuations in estradiol levels. Several studies suggest that migraines are associated with menstruation. Conclusion It appears that estrogen is very likely to play a key role in migraine pathogenesis, but seems to affect patients in different ways depending on their past medical history, age, and use of hormonal therapy. Further research is warranted to isolate the effects of estrogen in each unique patient population, and we believe that studies comparing menstruating women to postmenopausal women could help shed light in this area.